Inovasi Pendidikan Digital: Sosialisasi Penggunaan Media Sosial Dan Internet Bagi Siswa Sekolah Menuju Masa Depan Yang Produktif - Alwi Baharudin; Andre Kodarudin; Fajarudin Shidiq; Khoeroni Firdaus; Nurfalah Saeful Akbar; Muhammad Rizky Ripal; Noverius Telaumbanua; Pipim Ardianto; Rifki Halim; Ruyadi; Samsoni (CV. Multi Kreasi Media, 2023)
Digital education has become an integral part of the modern education system. Innovations in digital education have brought significant changes in how students learn and interact in schools. In an effort to prepare the students of SMK Perwira Bangsa for a productive future, it is necessary to carry out responsible socialization of the use of social media and the internet. This article explains the innovation of digital education in the form of socialization of the use of social media and the internet, and its impact on the development of students at SMK Perwira Bangsa.